2023
DOI: 10.1038/s41401-023-01080-z
|View full text |Cite
|
Sign up to set email alerts
|

GPR84 regulates pulmonary inflammation by modulating neutrophil functions

Abstract: Acute lung injury (ALI) is an acute, progressive hypoxic respiratory failure that could develop into acute respiratory distress syndrome (ARDS) with very high mortality rate. ALI is believed to be caused by uncontrolled inflammation, and multiple types of immune cells, especially neutrophils, are critically involved in the development of ALI. The treatment for ALI/ARDS is very limited, a better understanding of the pathogenesis and new therapies are urgently needed. Here we discover that GPR84, a medium chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…LPS, a cell wall component of Gram-negative bacteria, is found in various occupational dusts and air pollutants, and its elevated concentration causes high expression of various cytokines and chemokines in the human body, ultimately leading to the formation and aggravation of pneumonia. , To investigate the immunoinhibitory effect of MSC-EVs-PD-L1, we used LPS to induce ARDS in mice (Figure a). DiD-labeled MSC-EVs-PD-L1 were intratracheally injected into ARDS mice.…”
Section: Resultsmentioning
confidence: 99%
“…LPS, a cell wall component of Gram-negative bacteria, is found in various occupational dusts and air pollutants, and its elevated concentration causes high expression of various cytokines and chemokines in the human body, ultimately leading to the formation and aggravation of pneumonia. , To investigate the immunoinhibitory effect of MSC-EVs-PD-L1, we used LPS to induce ARDS in mice (Figure a). DiD-labeled MSC-EVs-PD-L1 were intratracheally injected into ARDS mice.…”
Section: Resultsmentioning
confidence: 99%
“…After dewaxing and hydration, HE staining was performed with hematoxylin and eosin, after which the sections were dehydrated and sealed under a microscope. Pathological analysis was performed according to Smith’s semiquantitative lung injury pathological scoring criteria as detailed in previous studies ( Smith et al., 1997 ; Wang et al., 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Further studies found that the activation of GPR84 strongly induced neutrophils to produce ROS by stimulating the activation of Lyn, AKT and ERK1/2 and the assembly of NADPH oxidase. The lack or blockage of GPR84 can significantly improve the pulmonary inflammation of ALI mice by reducing neutrophil infiltration and oxidative stress [ 62 ].…”
Section: The Impact Of Free Fatty Acids Uptake and Transportation On Alimentioning
confidence: 99%